2017
DOI: 10.5853/jos.2016.00675
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Good Outcome and Mortality After Stent-Retriever Thrombectomy in Patients With Acute Anterior Circulation Stroke

Abstract: Background and Purpose Predictive factors associated with stent-retriever thrombectomy for patients with acute anterior circulation stroke remain to be elucidated. This study aimed to investigate clinical and procedural factors predictive of good outcome and mortality after stent-retriever thrombectomy in a large cohort of patients with acute anterior circulation stroke.Methods We analyzed clinical and procedural data in 335 patients with acute anterior circulation stroke treated with stent-retriever thrombect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
44
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 25 publications
(39 reference statements)
13
44
1
Order By: Relevance
“…These models incorporate age and the severity of symptoms at presentation (NIHSS or Canadian Neurological Society score) and various variables such as prestroke mRS, ASPECTS, glucose at presentation, etiology of stroke, and medical history. However, previous studies have shown mTICI to be an important independent predictor of outcome [9-11] and this is not included in those models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These models incorporate age and the severity of symptoms at presentation (NIHSS or Canadian Neurological Society score) and various variables such as prestroke mRS, ASPECTS, glucose at presentation, etiology of stroke, and medical history. However, previous studies have shown mTICI to be an important independent predictor of outcome [9-11] and this is not included in those models.…”
Section: Discussionmentioning
confidence: 99%
“…Patient selection for IAT has been studied extensively [2, 6-8], whereas prognostication after IAT is relatively understudied [8-11]. Previous studies designed prediction models for outcome after ischemic stroke; however, the degree of reperfusion status was often not accounted for [19-23].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with those of several previous studies that evaluated the independent predictors of clinical outcome after mechanical thrombectomy in patients with acute ischemic stroke owing to intracranial large vessel occlusion, which found that a younger age, lower NIHSS score on admission, successful revascularization, and shorter procedure time were independent predictors of good outcom. [7][8][9][10] Here, incomplete revascularization was significantly associated with a poor clinical outcome. Several previous studies examined or mentioned potential differences in outcome between patients with a TICI of 3 versus a TICI of 2b.…”
Section: Discussionmentioning
confidence: 91%
“…Of the 69 included patients, 35 (50.7%) had atrial fibrillation, 36 (52.2%) had hypertension, and 15 (21.7%) had diabetes mellitus. The patients' mean DWI-ASPECTS was 7.5 (range, [3][4][5][6][7][8][9][10][11]. Among the 69 patients, the occluded vessel was the ICA in 24 patients (34.8%), the MCA M1 portion in 41 patients (59.4%), and the MCA M2 portion in 4 patients (5.8%).…”
Section: Baseline Characteristics Of the Patientsmentioning
confidence: 99%
See 1 more Smart Citation